Bork's Hoax: Antitrust and the Internet Market - James Alleman (International Telecommunications Society (ITS), 2021)
Robert Bork's Antitrust Paradox (1978) has been justification for lack of antitrust behavior for over four decades. His test essentially asks if consumers are harmed by the pricing practices of the firm in the market in which they purchase the good or service. Even if these firms are monopoly or oligopolies in their fields with huge economic rents, if they pass this test, no action is taken against them. "Bigness is not bad." This narrow view, inter alia, ignores two- and multisided markets (MSM) where the appearance of "no harm" is addressed to only one side of the market. The correct view is to examine all the markets impacting potential harm to consumers. It illustrates the harm which is "free" to the users, but advertisers pay dearly for the ability to micro-focus on potential consumers of their products. Facebook and Google are used as examples. This advertising cost is added into the sales price of the product, resulting in consumers being harmed by the embedded advertising costs in the products or services purchased. We argue here, using Bork's own criterion - except to expand it to the other side of the market and eliminating producer's surplus - that much needed antitrust action has been ignored by this narrow criterion. This analysis indicates that antitrust action is long overdue after considering two-sided markets. In addition, we argue that his "consumer welfare" criterion is misleading and liable to deceive, thus the hoax. The Bork critique is a hoax in two ways: Bork's analysis does not include the other side of the market. The cost of advertising has to be included in the price of the products being sold in order for the firm to remain in business. So, clearly, the price of goods and services is increased by the cost of advertising, thus reducing consumers' surplus. The second flaw is Bork's definition of "consumer welfare" - it includes the economic rents of the firm - all at a cost to consumers. Enhancing the wealth (profits) of corporations in the name of efficiency was not the purpose of the antitrust laws. We address the Bork Paradox on its own terms by examining the second side of the market which harms consumers indirectly by increasing the price of the products and services they purchase. Using the corrected Bork metric - both sides of the market and no producer's surplus - the estimated loss of consumers' welfare in 60.4 and 43.7 billion respectively from Google and Facebook, respectively.
Keywords: D42; D43; K21; L12; L13; L22; L51; L96; 330; Advertising; Antitrust; Bork; competition; consumers' surplus; digital markets; Information and Communications Technology (ICT); internet; platform economics; monopoly; regulation; two-sided/multisided markets